Factors Limiting Modeling Integration in the Mathematical Thinking-Representation - Ana Elizabeth González González; Osvaldo Jesús Rojas Velázquez; William Orlando Álvarez Araque (Migration Letters, 2023)
Mathematics teaching traditionally focuses on the mechanical learning of principles, formulas, and algorithms, disconnecting from the reality students face and their mathematical interpretation. Although there is research on numerical representation in various contexts, some educational centers have not yet incorporated modeling to strengthen mathematical thinking and understand real-world situations. This study seeks to identify the factors limiting modeling integration in mathematics teaching. It is a descriptive qualitative research based on a documentary review. The analysis found that the factors that restrict the adoption of modeling are socioeconomic, pedagogical, cognitive, and psychological. Therefore, it is necessary to implement pedagogical and didactic measures that encourage the active participation of students in the construction of mathematical knowledge. At the same time, educators need to act as guides and facilitators in this process.